Multiplicity of periodic bouncing solutions for generalized impact Hamiltonian systems - Delong Huang; Fei Guo (Boundary Value Problems, 2019)
Abstract Applying the Generalized Nonsmooth Saddle Point Theorem, we obtain multiple nontrivial periodic bouncing solutions for systems x¨=f(t,x) $\ddot{x}=f(t,x)$ with new conditions. In particular, we generalize the collision axis from x=0 $x=0$ to the axis x=a $x=a$, where a is an arbitrary constant.